Aluminum toxicity in roots of legume seedlings assessed by topological analysis - Simone Meredith Scheffer-Basso; Bruna Carla Priori (Acta Scientiarum. Agronomy, 2014)
The effect of aluminum (Al) on roots has been evaluated based on linear and weight measurements, but how this element influences the branching configuration of the root system remains unknown. The objective of this study was to assess aluminum toxicity in the roots of 21-day old seedlings from three forage legumes using topological analysis: Adesmia latifolia, Trifolium repens and T. pratense. The legumes were grown in dystrophic Red Latosol that had either been treated or not treated with dolomitic lime. This resulted in two Al saturation and pH treatments: (a) Al= 0%, pH= 6.2; and (b) Al= 16%, pH= 4.8. The following attributes were determined: number of first-order roots, external links (magnitude), total links in the longest unique path (altitude), total links in the primary root (primary root altitude), total exterior path length, total links, internal links, branching points and proportion of branching in the primary root. The topological variables were significantly reduced by Al for all of the legume species. There was a more randomized or dichotomous branching configuration in the seedlings grown in acid soil and A. latifolia was the most plastic of the species.